2013
DOI: 10.1159/000354634
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Validation of the iScore for Predicting Mortality and Early Functional Outcome in Ischemic Stroke Patients

Abstract: Background: We aimed to determine the accuracy of the iScore for predicting mortality and early disability following ischemic stroke in a French population-based study. Methods: All patients with acute ischemic stroke were identified among residents of the city of Dijon, France, between 2006 and 2011, using a population-based stroke registry. The 30-day iScore and 1-year iScore were calculated. A logistic regression model was used to assess the performance of the iScore for predicting both 30-day and 1-year mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…More recently, studies from Greece, Korea, China and other countries revealed good performance in other ethnic groups [16,17,18,19]. The present study provides some additional evidence of its application to a well-defined European population [11]. Together, the aforementioned points illustrate some of the benefits, caveats and limitations for outcome predictions using risk scores.…”
Section: What Are the Limitations Of The Study?supporting
confidence: 60%
See 1 more Smart Citation
“…More recently, studies from Greece, Korea, China and other countries revealed good performance in other ethnic groups [16,17,18,19]. The present study provides some additional evidence of its application to a well-defined European population [11]. Together, the aforementioned points illustrate some of the benefits, caveats and limitations for outcome predictions using risk scores.…”
Section: What Are the Limitations Of The Study?supporting
confidence: 60%
“…Béjot et al [11] evaluated the performance of the iScore in over 1,000 stroke patients, applying a population-based design in France. They found good performance of the iScore when applied to their patients: the C-statistic was 0.85 (95% CI: 0.82-0.89) for 30-day and 0.84 (0.81-0.87) for 1-year mortality.…”
Section: What Are the Limitations Of The Study?mentioning
confidence: 99%
“…8 The ASTRAL score, the DRAGON score, the iScore, the Six Simple Variables score, and the Get With The Guidelines (GWTG) score have been extensively validated in external data sets and sometimes for the prediction of outcomes other than the ones for which they were originally developed. 69,70,[82][83][84][85][86][87][88][89][90][91][92][93][94][95] These extended validations further increase the scores' reliability. The scores that are free of specialized laboratory tests or imaging techniques and include only simple parameters are more feasible for centers with limited resources.…”
Section: Advantages and Limitations Of The Prognostic Scoresmentioning
confidence: 90%
“…We included 18 relevant studies from 2374 hits that were retrieved through the electronic database search . The flow chart of study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the majority of studies were retrospective in design or post hoc analyses of prospectively collected clinical data, we were seldom able to judge whether the prognostic variables were collected early in the course of the presentation. Treatment pathways were seldom reported, with only three studies explicitly stating that participants received similar care . We recorded more complete reporting of the modality used in neuroimaging (12 studies), as well as amount of missing data (10 studies) (Table S2).…”
Section: Resultsmentioning
confidence: 99%